Does childhood experience of attention-deficit hyperactivity disorder symptoms increase sleep/wake cycle disturbances as measured with actigraphy in adult patients with bipolar disorder?. (3rd August 2019) - Prunas, C; Krane-Gartiser, K; Nevoret, C; Benard, V; Benizri, C; Brochard, H; Faedda, G; Geoffroy, PA; Gross, G; Katsahian, S; Maruani, J; Yeim, S; et al.
ABSTRACT: Childhood attention-deficit hyperactivity disorder (ADHD) is a common precursor of adult bipolar disorders (BD). Furthermore, actigraphy studies demonstrate that each disorder may be associated with abnormalities in sleep and activity patterns. This study investigates whether the presence or absence of self-reported childhood experiences of ADHD symptoms is associated with different sleep and activity patterns in adults with BD. A sample of 115 euthymic adult patients with BD was assessed for childhood ADHD symptoms using the Wender Utah Rating Scale (WURS) and then completed 21 days of actigraphy monitoring. Actigraphic measures of sleep quantity and variability and daytime activity were compared between BD groups classified as ADHD+ ( n = 24) or ADHD− ( n = 91), defined according to established cutoff scores for the WURS; then we examined any associations between sleep–wake cycle parameters and ADHD dimensions (using the continuous score on the WURS). Neither approach revealed any statistically significant associations between actigraphy parameters and childhood ADHD categories or dimensions. We conclude that the sleep and activity patterns of adult patients with BD do not differ according to their self-reported history of ADHD symptoms. We discuss the implications of these findings and suggest how future studies might confirm or refute our findings.